In-process measurement of the surface quality for a novel finishing process for polymer additive manufacturing - Syam, Wahyudin P.; Leach, Richard K.; Rybalcenko, Konstantin; Gaio, Andrȇ; Crabtree, Joseph (Elsevier, 2018)
In the last decade, there has been considerable growth in the production of end-use polymer parts and components using additive manufacturing methods. A wide range of polymers, from Nylon-12 to thermoplastic polyurethane polymers, can be processed with complex geometry tailored to specific function. However, due to the nature of the layer-by-layer process used in additive manufacturing, high roughness surfaces remain on the parts. To reduce the roughness of the surfaces, a proprietary post-processing method, developed by Additive Manufacturing Technologies, is applied to the surfaces. To monitor and control the finishing of the surfaces, an in-process surface detection instrument has been developed based on machine vision and machine learning. This paper presents the machine learning approach and the effectiveness of the instrument for in-process measurement of the finished surfaces.